1991
DOI: 10.2307/3577813
|View full text |Cite
|
Sign up to set email alerts
|

Late Cataractogenesis in Rhesus Monkeys Irradiated with Protons and Radiogenic Cataract in Other Species

Abstract: Rhesus monkeys (Macaca mulatta) which were irradiated at ca. 2 years of age with acute doses (less than or equal to 5 Gy) of protons (32-2300 MeV) are exhibiting the late progressive phase of radiation cataractogenesis 20-24 years after exposure, the period during which we have been monitoring the sequelae of irradiation of the lens. The median life span of the primate is approximately 24 years. Analogous late ocular changes also occur in a similar period of the lifetimes of New Zealand White (NZW) rabbits (Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…These studies employed whole-body irradiations of rhesus monkeys with several energies of protons ranging from 55 -2300 MeV to simulate SPE spectra. While cataract incidence (Lett et al 1991) and cancer incidence (Wood 1991) were well-documented along with general pathology, effects on the brain did not include behavior, and the only salient finding was an elevated incidence of astrocytoma and glioblastoma primarily due to 55 MeV protons. Davis et al (1962) reported results from male rhesus monkeys administered 60 Gy of 250 kVp X-rays during partial head exposure in two 30-Gy monthly fractions to either the anterior frontal lobes, inferior parietal lobe, or both.…”
Section: Previous Behavioral Studies With Irradiated Non-human Primatesmentioning
confidence: 99%
“…These studies employed whole-body irradiations of rhesus monkeys with several energies of protons ranging from 55 -2300 MeV to simulate SPE spectra. While cataract incidence (Lett et al 1991) and cancer incidence (Wood 1991) were well-documented along with general pathology, effects on the brain did not include behavior, and the only salient finding was an elevated incidence of astrocytoma and glioblastoma primarily due to 55 MeV protons. Davis et al (1962) reported results from male rhesus monkeys administered 60 Gy of 250 kVp X-rays during partial head exposure in two 30-Gy monthly fractions to either the anterior frontal lobes, inferior parietal lobe, or both.…”
Section: Previous Behavioral Studies With Irradiated Non-human Primatesmentioning
confidence: 99%
“…Additional late effects of protons or helium include cataract-induction [16,35,47,68,77,82] late retinal cell damage [117], endothelial cell loss in retinal microvessels [5] and optic nerve (125), loss of endocrine function [104] and immunological deficits [54][55][56]88]. The majority of these studies conclude that late effects induced by protons or helium ions are nearly equivalent to what one would expect from equivalent photon doses.…”
Section: Proton and Helium Radiation Therapymentioning
confidence: 99%
“…New Zealand white (NZW) rabbits at 8-10 weeks of age were exposed to a single dose of Fe particles and then the cataract index was followed for 6 years (Lett et al, 1991). No cataracts were observed in control animals, or animals irradiated with 0.5 Gy Fe particles, and only slight increases beginning at about 5 years were observed with a dose of 1 Gy.…”
Section: Cataractogenesismentioning
confidence: 99%
“…During the period 1964-1969, the United States Air Force and NASA irradiated almost 2,000 rhesus monkeys with protons, high energy electrons, or X-rays to determine the effects of a single dose, total body surface exposure on mortality, carcinogenesis, endometriosis and cataractogenesis (Wood, 1991;Fanton and Golden, 1991;Lett et al, 1991). The animals varied in age from 18 months to 3 years old, and have been followed periodically ever since.…”
Section: Monkeys (Macaca Mulatta)mentioning
confidence: 99%